2004
DOI: 10.1007/s00213-004-1892-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-l-carnitine reduces impulsive behaviour in adolescent rats

Abstract: The attention deficit/hyperactivity disorder (ADHD) can affect human infants and adolescents. One important feature of this disorder is behavioural impulsivity. This study assessed the ability of chronic acetyl-L-carnitine (ALC, saline or 100 mg/kg SC, plus 50 mg/kg orally) to reduce impulsivity in a validated animal model for ADHD. Food-restricted rats were tested during adolescence (postnatal days, pnd, 30-45) in operant chambers with two nose-poking holes, one delivering one food pellet immediately, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 78 publications
8
39
1
Order By: Relevance
“…Interestingly, instead of showing an exclusive preference (i.e., 100% for LL), they occasionally chose the alternative SS possibility. This finding, which replicated those of previous experiments in our lab (Adriani, Caprioli, et al, 2003;Adriani, Della Seta, et al, 2003;Adriani & Laviola, 2006;Adriani et al, 2004), indicates that animals express a constant and active patrolling over the two alternative possibilities, as they adaptively probe whether there is any change over time in the outcome associated with nose poking at the nonpreferred hole.…”
Section: Methods Subjectssupporting
confidence: 88%
“…Interestingly, instead of showing an exclusive preference (i.e., 100% for LL), they occasionally chose the alternative SS possibility. This finding, which replicated those of previous experiments in our lab (Adriani, Caprioli, et al, 2003;Adriani, Della Seta, et al, 2003;Adriani & Laviola, 2006;Adriani et al, 2004), indicates that animals express a constant and active patrolling over the two alternative possibilities, as they adaptively probe whether there is any change over time in the outcome associated with nose poking at the nonpreferred hole.…”
Section: Methods Subjectssupporting
confidence: 88%
“…As expected from previous studies (Adriani et al, , 2004, some rats showed no sign of sensitivity or reactivity to the increasing delay, and continued to prefer the LL option all along the task. A slight decrease towards indifference was evident at the two highest delays, but a clear-cut SS preference was never exhibited (see Table 3).…”
Section: Response Time and Ll Preference In The "Flat" Subgroupsupporting
confidence: 87%
“…Only three male siblings per litter were used in the present experiment, housed in pairs of non-siblings, and tested during the adolescent period (PND 30e44) in the intolerance-to-delay (ID) task. After the first four delay sessions, those rats (ten subjects) demonstrating insensitivity to delay were assigned to the delayinsensitive subgroup and discarded from the drug treatments (Adriani et al, , 2004. The delay-sensitive rats (twenty subjects) were randomly assigned to either challenge with 8-hydroxy-2(di-n-propylamino)tetralin (8-OH-DPAT, Sigma Aldrich, Milan, Italy, at the dose of 0.060 mg/kg) or saline injection for 3 days.…”
Section: Animal Subjects and Treatment Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now accepted that these paradoxical findings can be due to differences in experimental procedures (Cardinal et al, 2000), or particularly to a baselinedependent effect (Barbelivien et al, 2008). In our work, where the delay interval was signaled, increased choice for the large reinforcer could be expected for SIL rats, like it would be expected with amphetamine (Cardinal et al, 2000) and methylphenidate (Adriani et al, 2004). However, the slightly enhanced impulsivity of SIL rats shall be discussed in terms of the reduced motivation also found in the novelty seeking test.…”
Section: Impulsivity and Novelty Seekingmentioning
confidence: 48%